Circumcision in Bleeding Disorders: Improvement of Our Cost Effective Method with Diathermic Knife - Karaman, Muhammet Ihsan; Zulfikar, Bülent; Özturk, Metin Ishak; Koca, Orhan; Akyüz, Mehmet; Bezgal, Fikret (Urology Journal, 2014)
Purpose: Circumcision is a very common surgical procedure that has been performed for thousands of years. In this paper, we report the long-term results of circumcision performed by using diathermic knife on patients with bleeding diathesis and the amount of blood factors used. Materials and Methods: A total of 147 patients with bleeding diathesis circumcised under local anesthesia by using diathermic knife between 1996 and 2010 were recruited into this study. Age of the patients, type of the bleeding diathesis and the treatment protocols were recorded. Postsurgical infection and bleeding rates of 2 different factor replacement protocols were recorded. Results: Mean age of the patients was 11.5 years (range, 1.5-37 years). In the group of protocol 1 applied patients, 3 patients (4%) had bleeding and one patient had infection whereas in group of protocol 2, 4 patients (5.4%) had bleeding. The bleeding cases were taken under control after the factor replacement and elastic bandage. Conclusion: Whenever it is necessary for an individual to be circumcised for any reason whatsoever, we think that circumcision can be performed in the patients with bleeding diathesis with lower costs and complication rates by using diathermic knife and the protocol that we used.